Classification of Parkinson's disease stages with a two-stage deep neural network - Pedrero-Sánchez, José Francisco; Belda-Lois, Juan Manuel; Serra-Añó, Pilar; Mollà-Casanova, Sara; López-Pascual, Juan (Frontiers in Aging Neuroscience, 2023)
Parkinson's disease is one of the most prevalent neurodegenerative diseases. In the most advanced stages, PD produces motor dysfunction that impairs of basic activities of daily living such as balance, gait, sitting, or standing. Early identification allows healthcare personnel to intervene more effectively in rehabilitation. Understanding the altered aspects and impact on the progression of the disease is important for improving the quality of life. This study proposes a two-stage neural network model for the classifying the initial stages of PD using data recorded with smartphone sensors during a modified Timed Up & Go test. The proposed model consists on two stages: in the first stage, a semantic segmentation of the raw sensor signals classifies the activities included in the test and obtains biomechanical variables that are considered clinically relevant parameters for functional assessment. The second stage is a neural network with three input branches: one with the biomechanical variables, one with the spectrogram image of the sensor signals, and the third with the raw sensor signals. This stage employs convolutional layers and long short-term memory. The results show a mean accuarcy of 99.64% for the stratified k-fold training/validation process and 100% success rate of participants in the test phase. The proposed model is capable of identifying the three initial stages of Parkinson's disease using a two-minute functional test. The test easy instrumentation requirements and short duration make it feasible for use feasible in the clinical context.